HIFα as a target for different oncoproteins during carcinogenesis - V. A. Kobliakov (Успехи молекулярной онкологии)
The basic characteristics of tumours are ability for invasiveness and metastasis. These properties are realized due to destruction of intercellular matrix caused with acidification of intercellular area stimulated with transition from tissue respiration to glycolysis. The transition  to glycolysis in tumor cells is observed not only during hypoxic state how is realized in normal cells but also during oxygenation (Warburg  effect). It is accepted that by any carcinogenic action the activation of oncogenes or inactivation of genes – supressors occurs. As a result  it is permanent expression of oncoproteins and stimulation of tumour development. Different oncoproteins operate in different regulation systems at that they cause the same effect – tumour development.It is assumed that oncoproteins are not the ultimate factor in tumour development but there are existed some common element which is activated by different oncoproteins. In this review it is assumed that common element is HIFα (hypoxia-inducible factor α) transcription factor and it is discussed the mechanisms its activation by oncoproteins takes place in different signal systems.